Tribological Properties of Thermo-Reversible Gel-Lubricants Containing Solid Lubricants - Kazumi Sakai (Japanese Society of Tribologists, 2011)
Previously, we have reported tribological characteristics of a new unique Thermo-Reversible Gel-Lubricants (TR Gel-Lube), which consists of base fluids and gel agent. TR Gel-Lube has low friction property compared with conventional greases under mild lubricating conditions. However, under severe lubricating condition, extreme pressure (EP) property must be improved by some EP additives. In this study, addition of solid lubricants was investigated. Tribological properties were examined by some tribometers and various enhancements by Molybdenum disulfide, Melamine Cyanuric Acid and Boron Nitrides were observed. Mechanisms of the lubricity improvements were proposed by results of some chemical/physical analyses.